Genomic Evolution and Phylodynamics of the Species Orthomarburgvirus marburgense (Marburg and Ravn Viruses) to Understand Viral Adaptation and Marburg Virus Disease’s Transmission Dynamics - Claude Mambo Muvunyi; Nouh Saad Mohamed; Emmanuel Edwar Siddig; Ayman Ahmed (Pathogens)
In this review, we investigated the genetic diversity and evolutionary dynamics of the Orthomarburgvirus marburgense species that includes both Marburg virus (MARV) and Ravn virus (RAVV). Using sequence data from natural reservoir hosts and human cases reported during outbreaks, we conducted comprehensive analyses to explore the genetic variability, constructing haplotype networks at both the genome and gene levels to elucidate the viral dynamics and evolutionary pathways. Our results revealed distinct evolutionary trajectories for MARV and RAVV, with MARV exhibiting higher adaptability across different ecological regions. MARV showed substantial genetic diversity and evidence of varied evolutionary pressures, suggesting an ability to adapt to diverse environments. In contrast, RAVV demonstrated limited genetic diversity, with no detected recombination events, suggesting evolutionary stability. These differences indicate that, while MARV continues to diversify and adapt across regions, RAVV may be constrained in its evolutionary potential, possibly reflecting differing roles within the viral ecology of the Orthomarburgvirus marburgense species. Our analysis explains the evolutionary mechanisms of these viruses, highlighting that MARV is going through evolutionary adaptation for human-to-human transmission, alarmingly underscoring the global concern about MARV causing the next pandemic. However, further transdisciplinary One Health research is warranted to answer some remaining questions including the host range and genetic susceptibility of domestic and wildlife species as well as the role of the biodiversity network in the disease’s ecological dynamics.